Estudo da estabilidade térmica da liga Ca(Nb1/2Bi1/2)xTi1-xO3:(B2O3) para uso em antena ressoadora dielétrica (DRA) - Fernandes, Tatiana Sainara Maia (2012)
The field of wireless communication has undergone a revolutionary growth in recent decades. This is attributed to the invention of wireless mobile phones. The success of second generation (2G) services of cellular communication, motivates the development of broadband third generation (3G) mobile phones and other wireless products and services, such as Bluetooth. This work describes the development and characterization of two ceramic systems based on a matrix of calcium titanate (CaTiO3) with substitution of titanium ions by niobium ions associated with bismuth (Ca (Nb1/2Bi1/2) xTi1-xO3, x = 0.7 and 0.8), aiming the addition of B2O3 to reduce the sintering temperature and to improve densification, and thus verify the modifications on material properties, such as the temperature coefficient τf. The ceramic series are produced from solid state reaction with the use of high energy mechanical milling and heat treatment. The structural characterization was performed by Scanning Electron Microscopy (SEM) and Pycnometry. Experiments were done to evaluate the dielectric behavior of samples in the range of Microwave and Radio Frequency (room temperature and with temperature variation). Finally the material was tested as a dielectric resonator antenna, and posteriorly the results were simulated using HFSS program (Ansoft High Frequency Structure Simulator). The produced ceramics have had their electrical, dielectric and antenna properties quite affected with the addition of B2O3.